Glycosylated haemoglobin concentrations in mothers of large babies. Issue 6273 (25th April 1981) - Steel, J M; Thomson, P; Johnstone, F; Smith, A F
Abstract : Mothers who have big babies may have had abnormal glucose tolerance during pregnancy. Glycosylated haemoglobin (HbA1) concentrations were measured on the first or second day after delivery in 50 women who had had babies weighing over the 95th centile for gestational age and in 50 women who had had normal-sized babies (controls). Nine of the mothers of big babies but only one of the controls had an HbA1 concentration above the normal range. All the women had normal glucose tolerance and HbA1 concentrations six weeks after delivery. Measuring HbA1 concentration in the first two days after delivery in mothers of large babies may identify gestational diabetics.